The Role of Innovation Management in Driving Educational Technology Adoption in Emerging Economies - Elbadiansyah, E.; Sain, Zohaib Hassan; Aziz, Aulia Luqman; Thelma, Chanda Chansa; Abdullah, Nurul Annisa (International Journal of Humanities, Education, and Social Sciences, 2025)
The rapid socio-economic changes in emerging economies demand integrating educational technologies to improve learning outcomes and prepare students for the globalized economy. The successful adoption of these technologies relies on effective innovation management, which must address challenges such as limited infrastructure and varying technological literacy levels. This research investigates the role of innovation management in facilitating the adoption of educational technologies in emerging economies. It aims to identify strategies to overcome barriers to technology integration in education and analyze their impact on academic outcomes. A mixed-methods approach was employed, combining quantitative data from global databases such as the World Bank's EdStats and UNESCO's Institute for Statistics with qualitative insights from interviews and case studies in selected emerging economies, including India, Kenya, Brazil, and Nigeria. Statistical analyses revealed a positive correlation between the Innovation Support Index and the Educational Technology Adoption Rate. For instance, India and Brazil demonstrated higher adoption rates (78% and 80%, respectively) corresponding to robust innovation support systems. In contrast, countries with lower innovation indices, like Nigeria, showed significantly lower adoption rates (50%). The study concludes that strategic innovation management is critical for driving the successful adoption of educational technologies in emerging economies. It emphasizes the need for policymakers and academic leaders to prioritize the development of innovation support systems to foster a conducive environment for technology integration. Strengthening innovation support systems significantly enhances the adoption of educational technologies, offering a pathway to improved educational equity and economic growth in these regions.